Recent food prices movements: A time series analysis - Cooke, Bryce; Robles, Miguel (International Food Policy Research Institute, 2009)
From 2006 to mid-2008 the international prices of agricultural commodities increased considerably, by a factor larger than two. This upward trend in agricultural prices captured the world’s attention as a new food crisis was emerging. Several explanations for these movements in prices, ranging from demand-driven forces to supply shocks, have been provided by analysts, researchers, and development institutions. This paper is an attempt to empirically validate these explanations using time series econometrics and data at monthly frequency. We focus on the international price of corn, wheat, rice, and soybeans. First, we identify variables associated with the factors mentioned as causing the increase in these agricultural commodities prices. Second, we use time series analysis to try to quantitatively validate those explanations. The empirical work presented here includes first difference models and rolling Granger causality tests. Overall, our empirical analysis mainly provides evidence that financial activity in futures markets and proxies for speculation can help explain the observed change in food prices; any other explanation is not well supported by our time series analysis.